Arkadia dzieciństwa - dom na Kresach - Seul, Anastazja (1961- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Anastazja Seul`s article "The Arcadia of a childhood - home on Eastern Borderlands" presents world seen through the eyes of Henryka Paśnik, who spent her childhood on Eastern Borderlands of Poland, namely Andrzejowka village, next to Kowl town, present Ukraine. The author, based on memories of Paśnik published in her book "The Promise. History, written by life itself" (Czestochowa, 2014), describes to a reader several life stories of Poles who lived on Eastern part of pre-war Polish lands. Full of serenity, harmonious coexistence of variety of nations living together, people of Andrzejówka village honored their national traditions, treated others with respect and kindness. Anastazja Seul pictures children?s activities and work of adults, habits and customs of that particular village, religious ceremonies, Holydays and days of festivities, as well as beauty of the nature that helps to discover God in it.
Keywords: Kresy; Obrzędy religijne; życie wsi; przyroda; patriotyzm; tożsamość narodowa; literatura piękna; Eastern Borderlands; religious rites; life of a village; nature; national identity; belle-letters